Air pollution mitigation through yajna: Vedic and modern views - Devender Kumar (Environment Conservation Journal, 2019)
In the modern way, our way of life has come under the influence of a new type of air pollution, just as humans are bound to live in polluted environment outside the home due to heavy pollution factors like factory, power plants and excess use of vehicles. Today, in the time of new technology, it is almost impossible to imagine life without these devices like mobiles, laptop, fridge, microwave ovens, air conditioners etc there is no strong solution to the radiation generated at the time of production and consumption of these devices. At the time the solution to reduce internal and external air pollution is found in our Indian scriptures as YAGYA. Veda is the pillar of Indian culture and human life .facts mentioned in Vedas are proven and important in the CHANDOGYA UPNISHAD, Yagya has been described as the best means of resolving environment pollution. It is said that about Yagya that is removes all impurities and pollution and makes it pure. The Havan Samegri used in the Yagya is burnt in fire and spread everywhere with the help of air removes contaminated air and creates a fragrant environment. In the modern era, it has become clear from the researches on Yagya that the number of particulate matters(which is harmful for human body and are responsible for lungs and heart diseases) are decreased by sacrificing some special wood like mango etc. It was observed that after performance of Yagya there was a significant decrease in the indoor EMR (Electromagnetic Radiation) level indicating a utility of Yagya as nonconventional solution for reducing indoor EMR level. Foreign scientist TRILVERT has said in his research that the sweet material like sugar used in Yagya has extraordinary power to purify the air.